Comparative Literature in a Global Context: Politics, Academic Literature, and the Future of Comparativism - Bagdonė, Karolina (Colloquia, 2025)
David Damrosch 2020. Comparing the Literatures: Literary Studies in a Global Age, Princeton University Press, p. 392, ISBN 978-069-123-455-7
Keywords: -